High Prevalence of Azole-Resistant Aspergillus fumigatus in Adults with Cystic Fibrosis Exposed to Itraconazole - Burgel, Pierre-Régis; Baixench, Marie-Thérèse; Amsellem, Michaël; Audureau, Etienne; Chapron, Jeanne; Kanaan, Reem; Honoré, Isabelle; Dupouy-Camet, Jean; Dusser, Daniel; Klaassen, Corné H.; Meis, Jacques F.; Hubert, Dominique; et al. (Antimicrobial Agents and Chemotherapy, 2012)
Classifications Services AAC Citing Articles Google Scholar PubMed Related Content Social Bookmarking CiteULike Delicious Digg Facebook Google+ Mendeley Reddit StumbleUpon Twitter current issue AAC About AAC Subscribers Authors Reviewers Advertisers Inquiries from the Press Permissions & Commercial Reprints ASM Journals Public Access Policy AAC RSS Feeds 1752 N Street N.W. • Washington DC 20036 202.737.3600 • 202.942.9355 fax • journals@asmusa.org Print ISSN: 0066-4804 Online ISSN: 1098-6596 Copyright © 2014 by the American Society for Microbiology. For an alternate route to AAC .asm.org, visit: AAC